Outcome of Pterygium Excision with Pedunculated Conjunctival Flap versus Conjunctival Free Graft Surgery - Sireedhorn Kurathong (2022)
Purpose: To compare the surgical time and recurrence rate of pterygium excision with pedunculated conjunctival flap and conjunctival free graft surgery in primary pterygium. Methods: A nonrandomized prospective control study was performed in 45 eyes of 39 patients with pterygium from July 2006 to July 2008. Six patients had bilateral pterygium and 3 patients had double-head pterygium which pterygium excision with pedunculated conjunctival flap was performed at nasal site and conjunctival free graft at temporal site. Twenty-eight operations were performed by pedunculated conjunctival flap technique (group A) and 20 operations were performed by conjunctival free graft technique (group B) Results: There were 26 females (66.7%) and 13 males (33.3%). Pterygium involved right eye in 20 cases (44.4%) and left eye in 25 cases (55.6%). The mean age was 64 years, range 34-88 years. The mean followed-up time was 9.2 months, range 3-20 months, The average surgical time in group A was 35,83 minutes (range 20-60 minutes) that was significantly less than 65 minutes (range 35-90 minutes) in group B (p = 0.000). There was no significant difference of recurrent rate in group A (7.14%) and group B (20%) (p = 0.184). Conclusion: Although pedunculated conjunctival flap and conjunctival free graft surgery are both effective to reduce recurrence rate after pterygium surgery, the pedunculated conjunctival flap is more conjunctival-preserved and less surgical time consuming. This technique can be an alternative procedure for pterygium surgery, especially for glaucoma patients.